Prenatal development - Jampel, Barbara (Del Mar, Calif. : CRM/McGraw-Hill Films, 1974)
Explores the biology and the psychology of the developing fetus. Presents the latest theories and information about the fetus and the environmental influences within the mother's uterus
Keywords: Fetus; Prenatal influences